Professional competences of the European Union's teachers (Alliance) - Kshyshtof Jushchak (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the social and governmental changes of the late XXth - beginning XXIst century. It is noted that similar phenomena occur in the European Union's countries. Such processes are observed in the educational process in modern school, demanding restructuring process of thinking, awareness of the new reality, new tasks and functions of society. Key words: European union, professional competences, civilization, the educational process.